A new antimicrobial nor-friedelane-type triterpenoid and other constituents from Plectranthus glandulosus Hook. f. (Lamiaceae). Issue 18 (8th September 2022) - Tedonkeu, Alex Tchinda; Tamokou, Jean-De-Dieu; Mpetga, James D. Simo; Nzogong, Raissa Tioyem; Kengne, Irene Chinda; Hao, Xiao-Jiang; Tene, Mathieu
Abstract: Chemical investigation of the ethanol extract from the whole plant of Plectranthus glandulosus led to the isolation of a new nor-triterpenoid (1 ) along with seventeen known compounds (2–18 ) including seven triterpenoids, nine flavonoids and one steroid. Their structures were established on the basis of 1D- and 2D-NMR, IR, and MS experiments, and by comparison of their spectroscopic data with those of similar compounds reported in the literature. The EtOH extract and some isolated triterpenoids (1 –4 and 13) were subjected to in vitro antimicrobial assays against a panel of pathogenic microorganisms, including Gram-positive and Gram-negative bacteria, and fungi using broth microdilution method. The EtOH extract displayed moderate activity (MIC = 512 µg/mL) against Staphylococcus aureus MSSA1, Shigella flexneri SDINT and Cryptococcus neoformans H99. Compounds 1, 4 and 13 showed the most potent antimicrobial effect with MICs of 32–256 µg/mL. Graphical Abstract: UF0001